Pendekatan Aspek Hukum, Geomorfologi, dan Teknik Dalam Penentuan Batas Wilayah Laut Daerah - Heryoso Setiyono; Ibnu Pratikto; Hariyadi Hariyadi (Universitas Diponegoro, 2011)
Abstract The Indonesian Decree No 32 / 2004 related to the Local Authority justified the coastal region management to the province and or region. The Government law related to the coastline determination is not yet defined. Due to the problem, the international procedure of the coastline determination were descriptively analyzed base on the sea law, geomorphology and plan mapping.Key-words : regional coast line, maritime line, international sea law